Gli1‐induced deubiquitinase USP48 aids glioblastoma tumorigenesis by stabilizing Gli1. (16th June 2017) - Zhou, Aidong; Lin, Kangyu; Zhang, Sicong; Ma, Li; Xue, Jianfei; Morris, Saint‐Aaron; Aldape, Kenneth D; Huang, Suyun
Abstract: Aberrant activation of the Hedgehog (Hh) signaling pathway drives the tumorigenesis of multiple cancers. In this study, we screened a panel of deubiquitinases that may regulate the Hh pathway. We find that deubiquitinase USP48 activates Gli‐dependent transcription by stabilizing Gli1 protein. Mechanistically, USP48 interacts with Gli1 and cleaves its ubiquitin off directly. In glioblastoma cells, knockdown of USP48 inhibits cell proliferation and the expression of Gli1's downstream targets, which leads to repressed glioblastoma tumorigenesis. Importantly, USP48's effect on cell proliferation and tumorigenesis depends to some extent on Gli1. In addition, we find that the Sonic Hedgehog (SHH) pathway induces USP48 expression through Gli1‐mediated transcriptional activation, which forms thus a positive feedback loop to regulate Hh signaling. In human glioblastoma specimens, the expression levels of USP48 and Gli1 proteins are clinically relevant, and high expression of USP48 correlates with glioma malignancy. In summary, our study reveals that the USP48‐Gli1 regulatory axis is critical for glioma cell proliferation and glioblastoma tumorigenesis. Synopsis: Inappropriate Hedgehog signaling drives cancer formation. This study identifies USP48 as a new regulator of Gli1 stability and function and provides evidence that the Gli1‐USP48 regulatory axis is required for glioma cell growth and tumorigenesis. USP48 stabilizes Gli1 and promotes the expression of Gli1 downstream targets in glioma cells. USP48 interacts with Gli1 and deubiquitinates Gli1 directly. Hh signaling induces USP48 expression through transcriptional activation by Gli1. Depletion of USP48 inhibits glioblastoma cell growth and tumorigenesis, and expression of USP48 correlates with Gil1 expression in glioblastomas. Abstract : Inappropriate Hedgehog signaling drives cancer formation. This study identifies USP48 as a new regulator of Gli1 stability and function and provides evidence that the Gli1‐USP48 regulatory axis is required for glioma cell growth and tumorigenesis.